2022
DOI: 10.3390/life12040477
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of High-Resolution Ultrasound for the Evaluation of Capsular Width in Temporomandibular Joint Effusion

Abstract: Aim: The aim of this study was to evaluate if the increased temporomandibular joint (TMJ) capsular thickness, measured by ultrasound (US), is associated with the presence of effusion, diagnosed using MRI imaging. Materials and Methods: 102 patients with signs and symptoms of temporomandibular disorders were included in the study. Each patient underwent US and MRI examinations, 1 to 5 days following clinical examination. The US was performed with an 8–40 MHz linear transducer operating at 20 MHz. The MRI was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Similar to MRI, skilled operators and appropriate transducer frequency are required for the utilization of ultrasound in TMJ diagnosis. 33 Therefore, clinicians may choose the optimal diagnosing instrument based on their accessibility and diagnostic requirement. Meanwhile, some emerging technologies also deserve attention.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to MRI, skilled operators and appropriate transducer frequency are required for the utilization of ultrasound in TMJ diagnosis. 33 Therefore, clinicians may choose the optimal diagnosing instrument based on their accessibility and diagnostic requirement. Meanwhile, some emerging technologies also deserve attention.…”
Section: Discussionmentioning
confidence: 99%
“…The objective methods based on the measurement of representative anatomical landmarks were proposed to detect intra-articular abnormalities indirectly ( 29 ). The measurement methods were applied to obtain the reference values of normal joints ( 13 , 30 ), as well as to evaluate their association with joint effusion ( 31 - 34 ), joint pain ( 35 ), juvenile idiopathic arthritis (JIA) ( 36 , 37 ), and DD ( 29 , 38 ). The lateral capsular width was the most frequently used variable to investigate structural abnormalities in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…It could be explained by the larger disc thickness at the laterosuperior articular space. The capsular distension had previously been reported to be associated with intra-articular disorders or joint pain, which was detected indirectly as increased capsular width ( 31 , 32 , 34 , 35 ). Although some studies have implied that the capsular width tends to increase in patients with DD ( 29 , 34 ), its diagnostic value has remained controversial due to limited published data and variation of study design.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, facial pain localized to the temporomandibular joint (TMJ) often results from joint inflammation, leading to joint effusion [2][3][4]. This connection between arthralgia and joint effusion has been the focus of numerous studies [4][5][6][7][8][9]. Magnetic Resonance Imaging (MRI) is considered the gold standard for diagnosing TMD, given its ability to visualize soft tissue structures and the articular disc.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the disadvantages of MRI, such as its high costs, time consumption, and unsuitability for patients with claustrophobia or pacemakers, an alternative imaging technique is necessary [10]. Recent studies have suggested high-resolution ultrasonography (US) (using a transducer of at least 7.5 MHz or higher) as a viable substitute, as it is non-invasive, inexpensive, more comfortable for patients, and offers real-time imaging [9,[11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%